2023
DOI: 10.21203/rs.3.rs-3174972/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Study on the antipyretic activity and potential mechanism of Indigo Naturalis on lipopolysaccharide-induced fever rat model

xiaorong Xu,
Shengjie Huang,
Chuanhong Luo
et al.

Abstract: Background As a Traditional Chinese Medicine with an antipyretic effect, Indigo Naturalis (IN) has a long history of application in China. It is often used with other heat-clearing drugs to treat high fever in children, which is different from other heat-clearing medicines. But its antipyretic effect and mechanism have not been fully elucidated yet. And the heat-clearing development of IN lacks convincing current evidence. Methods This study aimed to uncover the antipyretic effect and mechanism of IN on infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…It is a dry powder processed from the leaves or stems of blue-producing plants, including Baphicacanthus cusia (Nees) Bremek, Polygonum tinctorium W.T.Aiton, and Isatis indigotica Fortune. Pharmacological studies have shown that IN had antipyretic, antibacterial, anti-inflammatory, and other pharmacological effects . Due to its excellent anti-inflammatory effects, IN is clinically used to treat UC, acute promyelocytic leukemia, and psoriasis. , The active ingredients of IN are mainly indigo, indirubin, and tryptanthrin (indolo­[2,1- b ]­quinoline-6,12-dione, TRYP) (Figure B).…”
Section: Introductionmentioning
confidence: 99%
“…It is a dry powder processed from the leaves or stems of blue-producing plants, including Baphicacanthus cusia (Nees) Bremek, Polygonum tinctorium W.T.Aiton, and Isatis indigotica Fortune. Pharmacological studies have shown that IN had antipyretic, antibacterial, anti-inflammatory, and other pharmacological effects . Due to its excellent anti-inflammatory effects, IN is clinically used to treat UC, acute promyelocytic leukemia, and psoriasis. , The active ingredients of IN are mainly indigo, indirubin, and tryptanthrin (indolo­[2,1- b ]­quinoline-6,12-dione, TRYP) (Figure B).…”
Section: Introductionmentioning
confidence: 99%